Transitions in the Cognitive Frailty States in Community-Living Older Adults: A 6-Year Prospective Cohort Study - Tang, Huiyu; Zhu, Huan; Sun, Qianqian; Qin, Hai; Wang, Shuang (Frontiers in Aging Neuroscience, 2021)
Backgrounds: Frailty is a multidimensional concept, including physical, cognitive, social, sensorial, psychological, and nutritional phenotypes. Among these phenotypes, cognitive frailty is the most widely investigated, which is related to many adverse health outcomes in older individuals. Whether cognitive frailty is dynamic or how these frail phenotypes interaction remains an open issue. We attempted to study the rate of these changes over time and their associated factors in a 6-year follow-up cohort. Methods: A total of 426 Chinese community-living older adults in Dujiangyan aged 65 years or older were recruited and followed-up in 3 visits 6 years apart. Frailty and cognitive function were assessed by the FRAIL scale and the Mini-Mental State Examination scale. Demographic information, geriatric syndrome and social interaction status were recorded. Rates of transitions in cognitive frailty states and associated risk factors were studied. We used the stepwise logistic regression model to analyze risk factors. Results: At baseline, 18.8% of participants were only PF or CI, and only 0.09% of participants were cognitive frailty. By the end of 6 years, 62 (14.5%) participants had died, the rates of only PF or CI group and cognitive frailty group increased to 36.2% and 3.3%, respectively. 199 (46.7%) participants had worsened into a worse state compared to the baseline. The multivariate regression analysis showed that older (OR=1.12, 95%CI=1.07-1.16, P＜0.001), smoker (OR=2.15, 95%CI=1.37-3.39, P=0.001), poor self-evaluation health status (OR=1.93, 95%CI=1.06-3.51, P=0.033), and malnutrition (OR=2.07, 95%CI=1.21-3.52, P=0.008) were risk factors for worsening, whereas willing to making new friends (OR=0.61, 95%CI=0.38-0.96, P=0.032) was associated with 38% lower chance of deterioration. Conclusion: Cognitive frailty is a dynamically changing state, which transitions may be influenced by multidimensions. Multidimensional monitoring of a wide range of events occurring in aging may be the best way to act early. We hope our study may serve as a starting point for redefining the definition of cognitive frailty by covering different frailty domains.